ANALISIS FEASIBILITY STUDY BALAI PENGEMBANGAN TERNAK SAPI PERAH DAN HIJAUAN MAKANAN TERNAK MENUJU BADAN LAYANAN UMUM DAERAH - Achmad Firman; Muhammad Hasan Hadiana (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
This research was carried out at the Center for Dairy Cattle and Forage Animal Feed, the Department of Food Security and Animal Husbandry, West Java Province. The purpose of this study is to identify potential revenues and costs from the production of dairy cow breeds and milk production from the Center for Dairy and Forage Cattle Development, and to identify potential opportunities for centers to become BLUDs based on their financial capabilities. The data used are secondary data from the center. The analysis method used in this research is the method of financial analysis which focuses on the net present value (NPV) and the internal rate of return (IRR) to see the business feasibility of this center. The results of this study indicate that dairy cows have not been used optimally but in this analysis, the capacity of the cowshed is used optimally. The projected investment and operational costs reach Rp. 16.8 billion and Rp. 3 billion, respectively. The projected revenue has a potential of more than IDR 5 billion per year. The results of the feasibility analysis show that the NPV value is IDR 237 million and an IRR of 12.24%. The Center for Dairy Cattle and Forage Forage can be upgraded to BLUD based on the criteria of the feasibility study.